Negative electrode for secondary battery and method for producing same
By setting a porous polymer layer on the negative electrode of the lithium-ion battery and forming a lithium-based material layer on it, the problems of fragility of lithium metal negative electrode and dendrite formation are solved, and the rigidity and stability of the negative electrode are improved, and the battery life is extended.
Patent Information
- Application Number
- JP2024544504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-08-28
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-08-28
AI Technical Summary
The negative electrode material of the existing lithium-ion battery is a lithium metal negative electrode that easily forms dendrites during charging and discharging, resulting in an increase in the thickness of the electrode, reducing the cycle characteristics and safety. At the same time, the fragility of the lithium metal itself makes it difficult to manufacture.
A porous polymer layer is provided on the carbon-based current collector and a lithium-based material layer is formed thereon. By opening a perforation in the porous polymer layer to enhance the adhesion between the lithium-based material and the carbon-based current collector, carbon-based materials such as graphite, graphene, carbon nanotubes, etc. are used to improve the rigidity and stability of the negative electrode.
It improves the rigidity and stability of the negative electrode, enhances the uniformity of lithium-based materials, extends the battery life and improves the cycle life.
Smart Images

Figure 2025503191000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a secondary battery and a method for producing the same, and more particularly to a negative electrode for a secondary battery having excellent rigidity and lithium plating properties and a method for producing the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0110407 filed on August 31, 2022, and Korean Patent Application No. 10-2022-0187919 filed on December 28, 2022, and the entire contents disclosed in the specification and drawings of said applications are incorporated herein by reference. [Background technology]
[0003] Recently, interest in energy storage technology is increasing. As the fields of application expand to include mobile phones, video cameras, and laptops, as well as the energy of electric vehicles, efforts in the research and development of electrochemical elements are becoming more and more concrete. From this perspective, electrochemical elements are the field that has attracted the most attention, and efforts in the development of rechargeable secondary batteries are the focus of attention. In addition, in order to develop such batteries, research and development efforts have been actively conducted recently on new electrode and battery designs in order to improve capacity density and specific energy.
[0004] Among the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of having a higher operating voltage and a much higher energy density than conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfur-acid-lead batteries.
[0005] Among these secondary batteries, lithium-sulfur (LiS) batteries have been attracting attention as a next-generation secondary battery that will replace lithium-ion batteries due to their high energy density. Lithium-sulfur batteries use sulfur-based materials as the positive electrode active material, and during discharge in the lithium-sulfur battery, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur, at which time sulfur converts from a ring-structured S8 to a linear-structured lithium polysulfide (Li2S2, Li2S4, Li2S6, Li2S8). The lithium-sulfur battery is characterized by a stepwise discharge voltage until polysulfide (PS) is completely reduced to Li2-S.
[0006] Lithium metal can be used as the negative electrode of a lithium secondary battery. However, when such lithium metal is used as the negative electrode, there are problems in that the high reactivity of lithium causes high reactivity with an electrolyte during charging and discharging, and as charging and discharging are repeated, dendrites are formed on the surface of the negative electrode, causing the electrode to become thick, and the cycle characteristics and safety are reduced. In addition, there is a problem in that it is difficult to manufacture lithium metal as the negative electrode due to the low rigidity of lithium metal. Summary of the Invention [Problem to be solved by the invention]
[0007] SUMMARY OF THE PRESENT DISCLOSURE ... It is therefore an object of the present invention to provide a negative electrode for a secondary battery having improved elongation, rigidity and safety, a method for producing the same, and a secondary battery including the negative electrode. [Means for solving the problem]
[0008] In order to achieve the above object, according to one aspect of the present invention, there is provided a negative electrode for a secondary battery having the following features.
[0009] The negative electrode for a secondary battery according to the first aspect includes a carbon-based current collector, a porous polymer layer disposed on at least one side of the carbon-based current collector, and a lithium-based material layer disposed on an upper surface of the porous polymer layer.
[0010] According to a second aspect, in the first aspect, the lithium-based material layer contains at least one of lithium metal and a lithium alloy.
[0011] According to a third aspect, in the first or second aspect, the lithium-based material layer is a lithium metal layer.
[0012] According to a fourth aspect, in any one of the first to third aspects, the porous polymer layer has one or more through holes formed therein, and the carbon-based current collector and the lithium-based material layer are bonded to each other via the through holes.
[0013] According to a fifth aspect, the method of the fourth aspect is characterized in that the area occupied by the through-holes formed in the porous polymer layer is 15% to 60% of the total area of the porous polymer layer.
[0014] According to a sixth aspect, in the third or fourth aspect, the through-holes formed in the porous polymer layer have a diameter of 0.5 cm to 3 cm.
[0015] According to a seventh aspect, in any one of the first to sixth aspects, the porous polymer layers are located on both sides of a carbon-based current collector.
[0016] According to an eighth aspect, in any one of the first to seventh aspects, the specific surface area of the carbon-based current collector is 50 m 2 / g or more.
[0017] According to a ninth aspect, in any one of the first to eighth aspects, the areal density of the carbon-based current collector is 100 g / m2 The present invention is characterized in that:
[0018] According to a tenth aspect, in any one of the first to ninth aspects, the carbon-based current collector layer is characterized in that it contains graphite, graphene, carbon nanotubes (CNTs), graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), or two or more of these.
[0019] According to an eleventh aspect, in any one of the first to tenth aspects, the porous polymer layer is characterized in that it contains polyethylene, polypropylene, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenyleneoxide, polyphenylenesulfidro, polyethylenenaphthalene, or two or more selected from these.
[0020] According to another aspect of the present invention, there is provided a method for producing a negative electrode for a secondary battery having the following features.
[0021] A method for producing a negative electrode for a secondary battery according to a twelfth aspect includes the steps of: laminating a carbon-based current collector, a porous polymer layer having one or more through-holes on at least one surface of the carbon-based current collector, and a lithium-based material layer on an upper surface of the porous polymer layer to form a laminate; and pressing the laminate using a rolling process.
[0022] According to a thirteenth aspect, in the twelfth aspect, the lithium-based material layer contains at least one of lithium metal and a lithium alloy.
[0023] According to a fourteenth aspect, in the twelfth or thirteenth aspect, the lithium-based material layer is a lithium metal layer.
[0024] According to a fifteenth aspect, in any one of the twelfth to fourteenth aspects, the pressing step is carried out at a temperature range of 180° C. or less.
[0025] According to a 16th aspect, in any one of the 10th to 15th aspects, in the pressing step, the lithium-based material layer and the carbon-based current collector are bonded via through holes formed in the porous polymer layer.
[0026] According to still another aspect of the present invention, there is provided a secondary battery having the following configuration.
[0027] A secondary battery according to a seventeenth aspect is a secondary battery including a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode according to any one of the first to eleventh aspects. Effect of the Invention
[0028] According to an embodiment of the present invention, the rigidity of a negative electrode for a secondary battery can be improved. In particular, in the present invention, a negative electrode for a secondary battery having improved stability, tensile strength, and elongation can be provided.
[0029] Furthermore, according to one embodiment of the present invention, it is possible to provide a negative electrode in which a lithium-based material is uniformly plated.
[0030] Furthermore, according to one embodiment of the present invention, the life of the negative electrode can be improved.
[0031] Furthermore, a secondary battery including the negative electrode for a secondary battery can have an improved cycle life.
[0032] In addition to these, the present invention can have various other effects, which will be described in the sections for each embodiment, and descriptions of effects that can be easily inferred by a person skilled in the art will be omitted.
[0033] The drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the above-described content of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0034] [Figure 1] FIG. 2 is a schematic cross-sectional view of a negative electrode for a secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a negative electrode for a secondary battery according to one embodiment of the present invention. [Diagram 3] FIG. 13 is a graph showing the measurement results of tensile strength for an embodiment of the present invention. [Figure 4] FIG. 1 is a diagram showing the results of measuring the tensile strength of a comparative example of the present invention. [Diagram 5] FIG. 1 is a diagram showing the evaluation results of cell performance for an example of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The present invention will be described in detail below with reference to the accompanying drawings. The terms and words used in the specification and claims are not to be interpreted as being limited to their ordinary or dictionary meanings, but are to be interpreted as having meanings and concepts according to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0036] Therefore, it should be understood that the embodiment described in this specification and the configurations shown in the drawings are merely the most preferred embodiment of the present invention and do not represent the entire technical idea of the present invention, and therefore there may be various equivalent and modified embodiments that can be substituted therefor at the time of this application.
[0037] In addition, throughout the specification, when a part "includes," "comprises," "has," or "has" a certain element, this does not mean that it excludes other elements, but that it may further include other elements, unless otherwise specified.
[0038] A negative electrode for a secondary battery according to one embodiment of the present invention includes a carbon-based current collector, a porous polymer layer disposed on at least one surface of the carbon-based current collector, and a lithium-based material layer disposed on an upper surface of the porous polymer layer.
[0039] Conventionally, lithium metal itself or a current collector such as copper foil and lithium metal stacked together have been used as the negative electrode for secondary batteries. However, when only lithium metal is used as the negative electrode, there are problems in that it is prone to wrinkling and has low rigidity.
[0040] In the present invention, the use of a carbon-based current collector in the negative electrode improves the elasticity of the negative electrode, improves the tensile strength, and improves the workability and processability of the negative electrode. In addition, compared to conventional lithium metal foil negative electrodes using lithium metal itself, a carbon material having current collecting ability is further used, which improves the cell discharge capacity and stabilizes the coulombic efficiency. In addition, compared to conventional copper foil current collectors, the carbon-based current collector is lighter, which minimizes the decrease in cell energy density associated with the introduction of the current collector.
[0041] In addition, in the present invention, by using a porous polymer layer in the negative electrode, the elongation rate and elasticity of the negative electrode can be further improved, and by suppressing contact between the carbon-based current collector and the bulk electrolyte, it is possible to prevent side reactions between the carbon-based current collector and the electrolyte, which also has the effect of improving the life of the cell.
[0042] Furthermore, in the present invention, the use of a porous polymer layer in the negative electrode can improve the tensile strength and elongation. In addition, the improvement in the tensile strength and elongation of the negative electrode can improve the life of the negative electrode and the capacity of the secondary battery, and can also increase the stability.
[0043] In one embodiment of the present invention, the porous polymer layer may be located on at least one side of the carbon-based current collector, specifically on at least one surface of the carbon-based current collector, and the lithium-based material layer may be located on an upper side of the porous polymer layer, specifically on at least the upper surface of the porous polymer layer.
[0044] FIG. 1 is a schematic cross-sectional view of a negative electrode 10 for a secondary battery according to one embodiment of the present invention.
[0045] 1, a porous polymer layer 200 is disposed on both sides of a carbon-based current collector 100. A lithium-based material layer 300 is disposed on the upper surface of each of the porous polymer layers 200.
[0046] In one embodiment of the present invention, when a porous polymer layer is located on at least one surface of a carbon-based current collector, the porous polymer layer may be located on the entire one surface of the carbon-based current collector, or may be located on only a portion of the one surface.
[0047] In one embodiment of the present invention, the porous polymer layer may be in direct contact with the carbon-based current collector and may be located on at least one side of the carbon-based current collector, or other layers may be located partially or entirely between the porous polymer layer and the carbon-based current collector. For example, lithium metal may be located between the carbon-based current collector and the porous polymer layer.
[0048] The lithium-based material layer may be located on the upper side of the porous polymer layer, specifically, on the upper surface of the porous polymer layer. More specifically, since a carbon-based current collector is located on the lower surface of the porous polymer layer, the lithium-based material layer may be located on the upper surface of the porous polymer layer.
[0049] For example, when the porous polymer layer is located on one side of the carbon-based current collector, the carbon-based current collector, the porous polymer layer, and the lithium-based material layer can be laminated in this order, or when the porous polymer layers are located on both sides of the carbon-based current collector, the first lithium-based material layer, the first porous polymer layer, the carbon-based current collector, the second porous polymer layer, and the second lithium-based material layer can be laminated in this order.
[0050] Furthermore, the lithium-based material layer may be located on the entire top surface of the porous polymer layer, or may be located on only a portion of the top surface.
[0051] In one embodiment of the present invention, the lithium-based material layer includes at least one of lithium metal and lithium alloy, and the lithium-based material layer may be a lithium alloy layer or a lithium metal layer. The lithium alloy includes an element capable of being alloyed with lithium, and examples of the element capable of being alloyed with lithium include Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and alloys thereof.
[0052] In the negative electrode for a secondary battery according to an embodiment of the present invention, the porous polymer layer may have one or more through holes formed therein.
[0053] The negative electrode for a secondary battery according to the present invention may have a structure in which a carbon-based current collector, a porous polymer layer, and a lithium-based material layer are laminated in this order. However, the adhesive strength between the carbon-based current collector and the lithium-based material layer may be stronger than the adhesive strength between the porous polymer layer and the lithium-based material layer used in the present invention. Therefore, in order to further improve the adhesive strength of the laminate, one or more through holes may be formed in the porous polymer layer so that the carbon-based current collector and the lithium-based material layer are in direct contact with each other through the through holes.
[0054] As described above, the lithium-based material layer and the carbon-based current collector can be in direct contact with each other via the through-holes, but the through-holes described in this specification should be distinguished from pores formed in the porous polymer layer itself.
[0055] The porous polymer layer itself has pores, and at least one of the pores may penetrate from one side of the porous polymer layer to the other side of the porous polymer layer. However, the pores may not be formed along the shortest path from one side of the porous polymer layer to the other side, and may instead connect from one side of the porous polymer layer to the other side along a complex path. Therefore, it is difficult for the lithium-based material layer and the carbon-based current collector to come into direct contact through the pores formed in the porous polymer layer itself. In contrast, the through-holes in the present invention may be separately drilled in the porous polymer layer so that the lithium-based material layer and the carbon-based current collector layer can come into direct contact with each other.
[0056] 2 is a schematic cross-sectional view of an anode 10 for a secondary battery according to an embodiment of the present invention. Referring to FIG. 2, a laminate may be formed by positioning a porous polymer layer 200 having through-holes 210 on at least one side of a carbon-based current collector 100, and positioning a lithium-based material layer 300 on the upper surface of the porous polymer layer 200 having through-holes 210. In this case, the lithium-based material layer 300 and the carbon-based current collector 100 are directly contacted and bonded via the through-holes 210 formed in the porous polymer layer 200, so that the adhesion between the layers of the laminate may be more effectively maintained.
[0057] In the negative electrode for a secondary battery according to an embodiment of the present invention, the through-holes formed in the porous polymer layer may penetrate the porous polymer layer vertically. When the through-holes penetrate the porous polymer layer vertically, the lithium-based material layer can be more efficiently contacted with the carbon-based current collector. However, the through-holes formed in the porous polymer layer are not necessarily limited to those that penetrate the porous polymer layer vertically, and any hole that allows the lithium-based material layer and the carbon-based current collector layer to be efficiently contacted through the through-holes may be used.
[0058] In the negative electrode for a secondary battery according to an embodiment of the present invention, the diameter of the through-hole formed in the porous polymer layer may be larger than the diameter of the pores formed in the porous polymer layer. For example, the diameter of the through-hole may be 0.5 cm to 3.0 cm, or 1.0 cm to 2.0 cm. When the diameter of the through-hole falls within the above range, the lithium-based material layer and the carbon-based current collector can be bonded to each other through the through-hole so as to exert a sufficient adhesive force.
[0059] The through-hole is preferably circular in shape. However, the present invention is not limited to a circular shape, and the through-hole may be formed in a variety of shapes such as a square, a triangle, etc. If the through-hole is not circular, the distance from the center of the through-hole to the furthest part may be 0.25 cm to 1.5 cm.
[0060] In the negative electrode for a secondary battery according to one embodiment of the present invention, the distance between the through holes formed in the porous polymer layer may be 0.5 cm to 1.5 cm. When the distance between the through holes falls within the above range, the lithium-based material layer and the carbon-based current collector can be bonded with sufficient adhesive strength.
[0061] In the negative electrode for a secondary battery according to an embodiment of the present invention, the area occupied by the through holes in the total area of the porous polymer layer may be 15% to 60% or 20% to 40%. When the area occupied by the through holes in the total area of the porous polymer layer falls within the above range, the tensile strength and elongation of the negative electrode are improved while improving the adhesive strength between the layers of the negative electrode laminate, and it is possible to maintain suitable elasticity and rigidity. The total area refers to the total surface area when the porous polymer layer is observed from above, and may refer to the area including the area occupied by the through holes of the porous polymer layer.
[0062] In the negative electrode for a secondary battery according to an embodiment of the present invention, the porosity of the porous polymer layer may be 40% to 70%. When the porosity is within the above range, ions can be smoothly conducted through the porous polymer layer, which is advantageous in ensuring sufficient ion conductivity.
[0063] In the negative electrode for a secondary battery according to one embodiment of the present invention, the specific surface area of the carbon-based current collector is 30 m 2 / g or more, 50m 2 / g or more, 80m 2 / g or more, 100m 2 / g or more, and 2 When the specific surface area of the carbon-based current collector falls within the above range, a surface area capable of sufficiently supporting the lithium negative electrode is ensured, which is advantageous in terms of lowering the current density per unit area and stabilizing the lithium or lithium plating.
[0064] In the negative electrode for a secondary battery according to one embodiment of the present invention, the areal density of the carbon-based current collector is 100 g / m 2 Below 70g / m2 Below 50g / m 2 Below 30g / m 2 Below 15g / m 2 or less than 8g / m 2 It can be less than 0.1 g / m 2 By keeping the surface density of the carbon-based current collector within the above range, it is possible to minimize the decrease in cell energy density due to the introduction of the current collector. The surface density is calculated by dividing the surface area (i.e., the external area) of the carbon-based current collector by its weight, assuming that the carbon-based current collector has no pores.
[0065] In the negative electrode for a secondary battery according to one embodiment of the present invention, the thickness of the carbon-based current collector may be 3 μm to 20 μm or 5 μm to 12 μm. When the thickness of the carbon-based current collector falls within the above range, it is possible to impart suitable elongation, rigidity, and elasticity to the negative electrode for a secondary battery according to the present invention.
[0066] In the negative electrode for a secondary battery according to an embodiment of the present invention, the carbon-based current collector may include graphite, graphene, carbon nanotube (CNT), graphite nanofiber (GNF), carbon nanofiber (CNF), activated carbon fiber (ACF), or two or more selected from the above. However, the carbon-based current collector is not limited to the above materials, and any commonly used carbon-based material may be used as the carbon-based current collector in the present invention.
[0067] In the negative electrode for a secondary battery according to an embodiment of the present invention, the carbon-based current collector may have a structure in which carbon-based materials are entangled with each other to have porosity. For example, the carbon-based current collector may have a structure of a carbon nanotube composite having porosity formed by carbon nanotubes being entangled with each other. The carbon-based current collector may be a mat type that forms a free-standing (i.e., self-supporting) film. Therefore, the carbon-based current collector can maintain its shape without a separate support.
[0068] In the negative electrode for a secondary battery according to an embodiment of the present invention, the carbon-based current collector may support a lithium-based material. Specifically, as the lithium metal moves during charging and discharging of the secondary battery, at least a portion of the lithium metal may be supported within the pores of the carbon-based current collector.
[0069] In the negative electrode for a secondary battery according to one embodiment of the present invention, the thickness of the porous polymer layer may be 6 μm to 20 μm, or 8 μm to 12 μm. When the thickness of the porous polymer layer falls within the above range, the elongation, tensile strength, and elasticity of the negative electrode for a secondary battery can be improved.
[0070] In the negative electrode for a secondary battery according to an embodiment of the present invention, the porous polymer layer may include polyethylene, polypropylene, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenyleneoxide, polyphenylenesulfidro, polyethylenenaphthalene, or two or more selected from the above. However, the porous polymer layer is not limited to the above materials, and various materials not described in this specification may be used as long as they are within the range of selection by a person skilled in the art.
[0071] In the negative electrode for a secondary battery according to one embodiment of the present invention, the thickness of the lithium-based material layer can be 10 μm to 80 μm, 10 μm to 60 μm, 20 μm to 60 μm, 20 μm to 40 μm, or 30 μm to 50 μm. When the thickness of the lithium-based material layer falls within the above range, it is possible to ensure sufficient capacity of the negative electrode.
[0072] A method for manufacturing a negative electrode for a secondary battery according to one aspect of the present invention includes the steps of forming a laminate by stacking a carbon-based current collector, a porous polymer layer having a plurality of through-holes on at least one surface of the carbon-based current collector, and a lithium-based material layer on an upper surface of the porous polymer layer, and pressing the laminate using a rolling process.
[0073] In the method for manufacturing a negative electrode for a secondary battery according to one embodiment of the present invention, the pressing step may be performed at 180° C. or less, 150° C. or less, or 120° C. or less, or may be performed at room temperature in the range of 20° C. to 60° C. or 20° C. to 30° C. When the pressing step is performed in the above temperature range, it is possible to prevent the lithium-based material such as lithium metal from melting, to suppress the formation of an oxide layer on the lithium-based material to act as a resistor, and to prevent the lithium from melting during the manufacturing process.
[0074] In the method for manufacturing a negative electrode for a secondary battery according to an embodiment of the present invention, the pressing step may be performed in a dry environment such as a dry room. For example, the pressing step may be performed in an environment where the dew point is maintained at −10° C. or less, −30° C. or less, or −45° C. or less. When such conditions are satisfied, it is possible to prevent the surface of the lithium-based material from being contaminated, such as when the lithium-based material reacts with moisture to generate a lithium hydroxide layer.
[0075] In the pressing step in the method for manufacturing a negative electrode for a secondary battery according to an embodiment of the present invention, the lithium-based material layer and the carbon-based current collector may be bonded to each other via through-holes formed in the porous polymer layer, and the lithium-based material layer is distorted by the pressing and drawn into the through-holes, thereby coming into contact with and being bonded to the carbon-based current collector layer.
[0076] A secondary battery according to one aspect of the present invention includes a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is a negative electrode for the secondary battery according to the present invention.
[0077] According to an embodiment of the present invention, the secondary battery may be a lithium secondary battery, which includes a lithium metal secondary battery, a lithium ion secondary battery, a lithium sulfur battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0078] According to one embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector.
[0079] The positive electrode current collector can generally be made to a thickness of about 3 μm to 500 μm. Such a positive electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes to the battery, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. The positive electrode current collector can also be formed with minute irregularities on its surface to increase the adhesive force of the positive electrode active material, and a wide variety of forms such as a film, sheet, foil, net, porous body, foam, and nonwoven fabric can be used as the positive electrode current collector.
[0080] The positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder polymer.
[0081] The positive electrode active material may contain sulfur (S). In this specification, the sulfur-containing material is referred to as a "sulfur-based compound". The sulfur-based compound may include, for example, any sulfur-containing compound that can be formed using a reduction reaction of inorganic sulfur (S8) or an oxidation reaction of lithium sulfide (Li2S), and more specifically, inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , an integer 2≦x≦8), disulfide compounds, carbon-sulfur polymers ((C2S y ) n , y=2.5 to 50, n≧2), lithium sulfide (Li2S), or two or more of these.
[0082] The positive electrode active material may preferably be a sulfur-carbon composite, which may include a porous carbon material and a sulfur-based compound supported on at least one of the inside of the pores of the porous carbon material and the outer surface of the porous carbon material.
[0083] The porous carbon material supports a sulfur-based compound as a positive electrode active material, provides a skeleton to which the sulfur-based compound can be uniformly and stably fixed, and improves the conductivity of the positive electrode. There are no particular limitations on the type of porous carbon material that can be used as long as it is a porous carbon material.
[0084] The porous carbon material may be generally prepared by carbonizing various carbon precursors. The porous carbon material may have pores with varying internal diameters, and the pores may have an average diameter of 1 nm to 200 nm, and the porosity may be in the range of 10% by volume to 90% by volume of the total volume of the porous carbon material. If the average diameter of the pores is less than the above range, the pore diameter is merely at the molecular level, and therefore impregnation with sulfur cannot be performed. Conversely, if the average diameter of the pores is greater than the above range, the mechanical strength of the porous carbon material may be weakened, making it unsuitable for application to the manufacturing process of an electrode.
[0085] The "average pore diameter" can be measured according to a known method for measuring the diameter of pores in a porous material in the art, and the measurement method is not particularly limited. For example, the pore diameter can be measured according to a scanning electron microscope (SEM), a field-emission scanning electron microscope, a laser diffraction method, or a Brunauer-Emmett-Teller (BET) method. Measurement using the laser diffraction method can be performed, for example, using a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000). Measurement using the BET method can be performed, for example, using an analyzer of the BELSORP series manufactured by BEL Japan, but is not limited thereto.
[0086] The term "porosity" refers to the ratio of the volume of pores to the total volume of any structure, and is expressed in units of %, and can be used interchangeably with terms such as void ratio, porosity, etc. In the present invention, the measurement of the porosity is not particularly limited, and may be measured, for example, according to a BET method using nitrogen gas or a mercury porosimeter and ASTM D2873 in accordance with one embodiment of the present invention.
[0087] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk-like, and any shape commonly used in lithium-sulfur batteries may be used without limitation.
[0088] The porous carbon material may have a porous structure or a high specific surface area, and may be any material commonly used in the art. For example, the porous carbon material may be any one or more selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto. Preferably, the porous carbon material may be carbon nanotubes.
[0089] The method for producing the sulfur-carbon composite is not particularly limited in the present invention, and may be a method commonly used in the art. For example, the sulfur and the porous carbon material may be simply mixed and then heat-treated to form a composite.
[0090] In addition to the above-mentioned composition, the positive electrode active material may further include at least one selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.
[0091] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, and the IIIA group elements may include Al, Ga, In, or Ti, and the IVA group elements may include Ge, Sn, or Pb.
[0092] The sulfur-carbon composite may be present in an amount of 50% by weight or more based on the total weight of the positive electrode. Specifically, the sulfur-carbon composite may be present in an amount of, for example, 80% by weight or more, 90% by weight or more, or 95% by weight or more based on the total weight of the positive electrode active material layer. Specifically, the sulfur-carbon composite may be present in an amount of 80% by weight to 100% by weight, more specifically, 85% by weight to 99% by weight, 90% by weight to 99% by weight, 95% by weight to 98% by weight, 95% by weight to 97% by weight, or 96% by weight based on the total weight of the positive electrode active material layer.
[0093] In one embodiment of the present invention, the binder polymer holds the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to each other to further enhance the binding strength therebetween. Any binder polymer known in the art may be used.
[0094] For example, the binder polymer may be any one or a mixture or copolymer of two or more selected from the group consisting of polyacrylic acid (PAA), polyvinylidene fluoride (PVdF), polyvinylidene fluoride-based polymers containing at least one vinylidene fluoride repeating unit, polytetrafluoroethylene (PTFE), or a fluororesin-based binder including a mixture of two or more of these; rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isophrene rubber; acrylic binders; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.
[0095] In one embodiment of the present invention, the content of the binder may be 1 wt% to 10 wt% based on the total weight of the positive electrode active material layer. If the content of the binder is less than the above range, the physical properties of the positive electrode may be deteriorated, and the positive electrode active material and the conductive material may fall off, and if the content exceeds the above range, the ratio of the positive electrode active material and the conductive material in the positive electrode may relatively decrease, and the capacity of the battery may decrease. Therefore, it is preferable to determine an appropriate content within the above range.
[0096] In an embodiment of the present invention, the conductive material is a material that electrically connects an electrolyte and a positive electrode active material to function as a path through which electrons move from a current collector to the positive electrode active material. The conductive material is a component of an electrode that is physically distinct from carbon contained in the sulfur-carbon composite, and may be any conductive material without limitation.
[0097] The conductive material may be, for example, carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, thermal black, or carbon black; carbon derivatives such as carbon nanotubes or fullerene; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.
[0098] In one embodiment of the present invention, the content of the conductive material may be 1 wt% to 10 wt% based on the total weight of the positive electrode active material. If the content of the conductive material is less than the above range, the voltage and capacity are reduced because electrons are difficult to transfer between the positive electrode active material and the current collector. On the other hand, if the content exceeds the above range, the proportion of the positive electrode active material is relatively reduced, which may reduce the total energy (charge) of the battery, so it is preferable to determine an appropriate content within the above range.
[0099] In one embodiment of the present invention, the separator separates or insulates the positive electrode and the negative electrode from each other and transports lithium ions between the positive electrode and the negative electrode, and may be made of a porous, non-conductive or insulating material. Any material that is commonly used as a separator in a lithium secondary battery may be used without any particular limitation. Such a separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.
[0100] It is preferable that the separator has low resistance to the movement of electrolyte ions and has excellent moisture-absorbing ability for the electrolyte.
[0101] In one embodiment of the present invention, the separator may include a porous substrate, and the porous substrate may be any porous substrate commonly used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric or a polyolefin-based porous membrane made of high-melting-point glass fiber, polyethylene terephthalate fiber, or the like may be used, but is not limited thereto.
[0102] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate generally used in electrochemical devices can be used. For example, the porous substrate can be made of a material selected from the group consisting of polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyamides, polyacetals, polycarbonates, polyimides, polyether ether ketones, polyether sulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalenes, polytetrafluoroethylenes, polyvinylidene fluorides, polyvinyl chlorides, and the like. The material may include at least one material selected from the group consisting of polyparaphenylene chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylate.
[0103] In one embodiment of the present invention, the thickness of the porous substrate is not particularly limited, but may be 1 μm to 100 μm, preferably 5 μm to 50 μm. Although the thickness of the porous substrate is not limited to the above range, if the thickness is excessively thinner than the lower limit, there is a concern that the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.
[0104] In one embodiment of the present invention, the average diameter and porosity of the pores present in the porous substrate are also not particularly limited, and may be 0.001 μm to 50 μm and 10 vol % to 95 vol %, respectively.
[0105] In one embodiment of the present invention, the separator may further include a porous coating layer formed on at least one surface of the porous substrate, the porous coating layer including inorganic particles and a binder. The inorganic particles and binder included in the porous coating layer may be any inorganic particles and binder that are commonly used in the porous coating layer of a separator, and the manufacturing method thereof is also not particularly limited.
[0106] In one embodiment of the present invention, the electrolyte solution includes a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt.
[0107] The lithium salt may be any of those commonly used in electrolytes for secondary batteries, such as LiNO3 and LiTFSI, without any limitations. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P- , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - Any one selected from the group consisting of the following can be used.
[0108] The organic solvent contained in the electrolytic solution may be any commonly used organic solvent without any particular limitation. Representative examples include propylene carbonate, ethylene carbonate, dimethyl ether (DME), 1,3-dioxolane (DOL), diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfite, and tetrahydrofuran.
[0109] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents having a high dielectric constant and are suitable for use since they can dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, making them even more suitable for use.
[0110] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are normally included in electrolytes.
[0111] According to an embodiment of the present invention, a lithium secondary battery may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and then injecting an electrolyte therein. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed to manufacture a lithium secondary battery.
[0112] The present invention will be described in detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples.
[0113] Example 1 A lithium metal foil having a thickness of 50 μm was prepared as the first lithium metal layer, a polyethylene porous film having a thickness of 10 μm was prepared as the first porous polymer layer, carbon nanotubes having a thickness of 10 μm were prepared as the carbon-based current collector, a polyethylene porous film having a thickness of 10 μm was prepared as the second porous polymer layer, and a lithium metal foil having a thickness of 50 μm was prepared as the second lithium metal layer, and laminated in this order, and pressed at 25 ° C. using a rolling (roll press) process to manufacture a negative electrode. At this time, the first porous polymer layer and the second porous polymer layer had one or more through holes, and the area occupied by the through holes formed in the first porous polymer layer and the second porous polymer layer was 50% of the total area of the porous polymer layer, and the diameter of the through hole was 1.9 cm.
[0114] Comparative Example 1 A lithium metal foil having a thickness of 100 μm was prepared as the negative electrode.
[0115] Comparative Example 2 A lithium metal foil having a thickness of 50 μm was prepared as the first lithium metal layer, a carbon nanotube film having a thickness of 10 μm was prepared as the carbon-based current collector, and a lithium metal foil having a thickness of 50 μm was prepared as the second lithium metal layer. These were laminated in this order and pressed together using a rolling (roll press) process at 25°C to prepare a negative electrode.
[0116] Example 2 <Preparing the negative electrode> A negative electrode similar to that produced in Example 1 was prepared.
[0117] <Manufacturing lithium-sulfur batteries> A sulfur-carbon composite in which sulfur is supported on carbon nanotubes was prepared as a positive electrode active material. At this time, the weight ratio of carbon nanotubes to sulfur was set to 1:3. Polyacrylic acid (PAA) was mixed with the composite as a binder and carbon fiber as a conductive material to prepare a positive electrode slurry. At this time, the weight ratio of the positive electrode active material, conductive material, and binder was 88:5:7.
[0118] The prepared slurry was coated on an aluminum foil using a Matisse coating device, dried at a temperature of 50° C. for 24 hours, and then rolled to prepare a positive electrode.
[0119] As an electrolyte, a mixture was prepared by dissolving lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a concentration of 0.75 M and 1 wt% lithium nitrate (LiNO3) in an organic solvent consisting of 1,3-dioxolane and dimethyl ether (DOL:DME = 1:1 (volume ratio)).
[0120] The prepared positive electrode and negative electrode were positioned to face each other, and a polyethylene separator having a thickness of 16 μm and a porosity of 46% was interposed between them, and the resulting battery was placed in a pouch-type battery case. The electrolyte was then injected to prepare a lithium-sulfur battery.
[0121] Comparative Example 3 A lithium-sulfur battery was produced in the same manner as in Example 2, except that the negative electrode prepared in Comparative Example 1 was used as the negative electrode.
[0122] Experimental example 1: Tensile strength experiment Tensile strength was measured according to ASTM D-412 B.
[0123] Test pieces were prepared from the negative electrodes prepared in Example 1 and Comparative Examples 1 and 2, so as to conform to the standard of ASTM D-412 B. Then, tests were performed on each test piece using a Universal Testing Machine (UTM) and a 100 N load cell.
[0124] A strain rate of 0.01 mm / s was applied to each test piece, and the maximum stress value was measured to determine the tensile strength, which is shown in Table 1.
[0125] [Table 1]
[0126] FIG. 3 shows the measurement results of the tensile strength of the negative electrode in Example 1, and FIG.
[0127] Referring to Table 1, FIG. 3 and FIG. 4, it can be seen that the tensile strength of Example 1 is significantly increased compared to Comparative Example 1. It can be seen that the negative electrode of Comparative Example 1 has low rigidity because only lithium metal foil is present, and as a result, it is significantly elongated as it is distorted. The elongation length at break of Example 1 is significantly increased compared to Comparative Example 2. This is due to the fact that Example 1 includes a porous polymer layer, which increases the elongation rate.
[0128] Experimental example 2: Capacity retention rate experiment FIG. 5 is a graph showing the results of evaluating the cell performance of the lithium-sulfur batteries according to Example 2 and Comparative Example 3.
[0129] The lithium-sulfur batteries according to Example 2 and Comparative Example 3 were charged (0.3 C, CC mode) and discharged (0.5 C, CC mode) at 25° C., and the retention rate of the discharge capacity was calculated according to the following formula.
[0130] Discharge capacity retention rate (%) = [(discharge capacity at one cycle - discharge capacity at n cycles) / discharge capacity at one cycle] x 100
[0131] The lithium-sulfur battery of Example 2 maintained a capacity retention of 80% or more even after 250 cycles, whereas the lithium-sulfur battery of Comparative Example 3 was found to rapidly decrease in capacity retention before reaching 100 cycles.
[0132] As described above, the present invention has been described using limited embodiments and drawings, but the present invention is not limited to these, and it goes without saying that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention belongs within the technical spirit of the present invention and the equivalent scope of the claims.
Claims
1. A carbon-based current collector; a porous polymer layer located on at least one surface of the carbon-based current collector; a lithium-based material layer located on an upper surface of the porous polymer layer; 13. A negative electrode for a secondary battery comprising:
2. The negative electrode for a secondary battery according to claim 1 , wherein the lithium-based material layer includes at least one of lithium metal and a lithium alloy.
3. 2. The negative electrode for a secondary battery according to claim 1, wherein the lithium-based material layer is a lithium metal layer.
4. 2. The negative electrode for a secondary battery according to claim 1, wherein the porous polymer layer has one or more through holes formed therein, and the carbon-based current collector and the lithium-based material layer are bonded to each other via the through holes.
5. 5. The negative electrode for a secondary battery according to claim 4, wherein an area of the through holes formed in the porous polymer layer is 15% to 60% of an entire area of the porous polymer layer.
6. 5. The negative electrode for a secondary battery according to claim 4, wherein the through-holes formed in the porous polymer layer have a diameter of 0.5 cm to 3 cm.
7. The negative electrode for a secondary battery according to claim 1 , wherein the porous polymer layer is located on both sides of the carbon-based current collector.
8. The specific surface area of the carbon-based current collector is 50 m 2 The negative electrode for a secondary battery according to claim 1 , wherein the anode has a molecular weight of 1000 or more.
9. The areal density of the carbon-based current collector is 100 g / m 2 2. The negative electrode for a secondary battery according to claim 1, wherein:
10. 2. The negative electrode for a secondary battery according to claim 1, wherein the carbon-based current collector comprises graphite, graphene, carbon nanotubes (CNTs), graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), or two or more thereof.
11. The porous polymer layer may be made of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, etc.
2. The negative electrode for a secondary battery according to claim 1, comprising at least two selected from the group consisting of polyphenylene sulfide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfidro, and polyethylene naphthalene.
12. A step of laminating a carbon-based current collector, a porous polymer layer having one or more through holes on at least one surface of the carbon-based current collector, and a lithium-based material layer on an upper surface of the porous polymer layer to form a laminate; compressing the laminate using a rolling process; A method for producing a negative electrode for a secondary battery, comprising the steps of:
13. The method for manufacturing a negative electrode for a secondary battery according to claim 12, wherein the lithium-based material layer includes at least one of lithium metal and a lithium alloy.
14. The method for producing a negative electrode for a secondary battery according to claim 12, wherein the lithium-based material layer is a lithium metal layer.
15. The method for producing a negative electrode for a secondary battery according to claim 12 , wherein the pressing step is performed at a temperature range of 180° C. or less.
16. 16. The method for producing a negative electrode for a secondary battery according to claim 12, wherein in the pressing step, the lithium-based material layer and the carbon-based current collector are bonded via a through hole formed in the porous polymer layer.
17. A secondary battery including a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte, The negative electrode of claim 1 .
Citation Information
Patent Citations
Lithium composite electrode as well as preparation method and application thereof
CN112701293A
lithium secondary battery
JP1993275118A
Lithium metal anode for lithium battery
JP2004134403A
Battery
JP2014515546A
Lithium electrodes and lithium secondary batteries containing them
JP2017517853A